PELATIHAN STRATEGI BRANDING DAN DIGITAL MARKETING SERTA SOSIALISASI KREDIT USAHA RAKYAT - I.G.N.O. Panasea; I.W.G.W.P. Anggara; A.A.N.A. Kresnandra; I.M.A.P. Wistawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Nongan Village, Karangasem has so many potentials that can be improve, such as: tourism, agriculture, and culinary. Tourism sector of Nongan Village engaged in agro-tourism, such as hills, river, and the other tourism object. In addition, Nongan Village also has potential in the agricultural sector with potential commodities in the form of snake fruit, coconut, rice, and tubers. Not only tourism and agricultural, Nongan Village also has potential in other field, like in the culinary sector with their pia product. However, until now these potentials tend to be developed conventionally, so that business development is still limited. In the era 4.0, everything has been transformed into all digital. Coupled with the COVID-19 pandemic, the potentials for digital business development is very promising. With digital marketing training for SMEs in the village, the authors hope that the output of this service is in the form of implementing digital marketing in developing its business. This training does not only focus on the potentials mentioned above, rather it’s open to every potential that exists in the village of Nongan. Keywords: branding, digital marketing, KUR socialization, SMEs